Relationship between Physical Activity Levels and Academic Performance in Adolescents from Serbia - Tamara Ilić; Stefan Stojanović; Doroteja Rančić; Bojan Milenko Jorgić; Rareș Stănescu Cristian; Daniel Andrei Iordan; Codreanu Corneliu Mircea; Stoica Leonard; Ilie Onu (Children)
Background/Objectives: Today’s high school students often engage in sedentary behavior by choosing passive activities during leisure time. Increasing research shows that regular physical activity (PA) provides benefits beyond physical health, especially important during childhood and adolescence. Our study investigated the association between physical activity levels and academic performance (AP) in Serbian adolescents. Methods: We selected a sample of 836 fourth-grade high school students (avg. 17.9 ± 0.7 years old) who completed the IPAQ (short-version) and the Academic Performance Scale. Data analysis was conducted using IBM SPSS 21.0. Due to non-normal data distribution, Spearman’s correlation was used and hierarchical regression analysis to assess the association between PA and AP. Results: The findings revealed significant correlations between vigorous, moderate and light PA, as well as overall units of metabolic equivalent of task (METs), with AP (p-values: 0.000, 0.005, 0.021, 0.004, respectively), although with weak correlation coefficients (0.127, 0.098, 0.080, 0.181, respectively). Vigorous PA influenced AP by 10.1%, moderate PA by 8.2%, and light PA by 11.4%. Conclusions: These results suggest that adolescents engaging in higher PA levels tend to have better AP. This finding indicates a substantial association between PA levels and AP, with both moderate and vigorous PA showing a positive correlation and influence. Further investigation is necessary to comprehensively grasp the link between light PA and AP.